Effects of feeding selected rumen-protected fats on reproductive performance of male malin sheep - Ahmad, Mohd Hafizal (2019)
Rumen protected fat have been used in the livestock industry to increase the energy density of the animal feed to compensate the energy deficiency in dairy animal but not normally feed to male animals. Male animals that are used for breeding also required a lot of energy for physical activity and its reproductive system. Though, knowledge on the effect of rumen protected fats to the reproductive system in the male sheep is still limited. Therefore, this study purpose is to evaluate the effects of rumen protected fat (RPF) that is high in fatty acid on reproductive system in Malin rams. Twenty adult Malin rams were randomly assigned to four group namely, T1: control, T2: 2% prilled fat, T3: 2% calcium salt fatty acid (casa) and T4: 2% canola oil respectively. Prilled fat and calcium salt fatty acid (casa) are rumen protected fat made from palm oil. Body weight gain and average daily gain shown no significant different (P>0.05) during the experimental period and yet, there was a tendency higher body weight gain in animal fed with calcium salt fatty acid (casa). Results showed that rams received prilled fat have significant higher (P<0.05) semen volume compare to casa and canola groups. The sperm concentration of animals received canola oil shown a significant higher (P<0.05) than animals received prilled fat and casa. There are significant increased (P<0.05) in the sperm membrane integrity and live sperm in prilled and casa group than control. Increase semen volume, sperm membrane integrity and live sperm in prilled and casa group indicated that more fatty acid reach the small intestine for absorption causing more energy production thus improving sperm quality. Testosterone level, testicular traits and histological structure of testes showed no significantly difference (P>0.05) among all group. This suggest that usage of fat supplement not only depend on nature or type of fat but also on the amount of fat added in the feed to affect the testosterone production and spermatogenesis in the testes. In conclusion, inclusion of rumen protected fats as a supplement to adult Malin rams have improved the semen volume, sperm membrane integrity and live sperm without affecting testosterone production and spermatogenesis.